Pediatric tinnitus: Incidence of imaging anomalies and the impact of hearing loss. (December 2017) - Kerr, Rhorie; Kang, Elise; Hopkins, Brandon; Anne, Samantha
Abstract: Objective: Guidelines exist for evaluation and management of tinnitus in adults; however lack of evidence in children limits applicability of these guidelines to pediatric patients. Objective of this study is to determine the incidence of inner ear anomalies detected on imaging studies within the pediatric population with tinnitus and evaluate if presence of hearing loss increases the rate of detection of anomalies in comparison to normal hearing patients. Methods: Retrospective review of all children with diagnosis of tinnitus from 2010 to 2015 ;at a tertiary care academic center. Results: 102 pediatric patients with tinnitus were identified. Overall, 53 patients had imaging studies with 6 abnormal findings (11.3%). 51/102 patients had hearing loss of which 33 had imaging studies demonstrating 6 inner ear anomalies detected. This is an incidence of 18.2% for inner ear anomalies identified in patients with hearing loss (95% confidence interval (CI) of 7.0–35.5%). 4 of these 6 inner ear anomalies detected were vestibular aqueduct abnormalities. The other two anomalies were cochlear hypoplasia and bilateral semicircular canal dysmorphism. 51 patients had no hearing loss and of these patients, 20 had imaging studies with no inner ear abnormalities detected. There was no statistical difference in incidence of abnormal imaging findings in patients with and without hearing loss (Fisher's exact test, p ;= ;0.072.) Conclusion: There is a high incidence of anomalies detected in imaging studies done in pediatric patients with tinnitus, especially in the presence of hearing loss.